Prevalence of Metabolic Syndrome in individuals with Type 2 Diabetes Mellitus - José Cláudio Garcia Lira Neto; Mayra de Almeida Xavier; José Wicto Pereira Borges; Márcio Flávio Moura de Araújo; Marta Maria Coelho Damasceno; Roberto Wagner Júnior Freire de Freitas
ABSTRACT Objective: to identify the prevalence of Metabolic Syndrome and its components in a population of patients with type 2 Diabetes Mellitus. Method: a cross-sectional study was conducted with 201 diabetic patients. A descriptive analysis and Chi-square and Fisher's exact tests ( p <0.05) were performed. Results: the majority of participants were females and overweight, with a mean age of 63.1 years and a low level of education, and categorized as physically inactive. Of all individuals investigated, 50.7% were diagnosed with Metabolic Syndrome and 92% had at least one of the syndrome components with values beyond those recommended. Conclusion: it is essential to take preventive actions and develop studies that help to identify the factors associated with this syndrome.